Особенности построения диагностических функций в электронном блоке микропроцессорной системы управления гидромеханической трансмиссией на современных транспортных средствах - Александров, Евгений Евгеньевич; Стримовский, Сергей Викторович (НТУ "ХПИ", 2007)
It is offered design the microprocessor control system hydromechanical transmissions with extended diagnostic functions due to analysis of the greater number parameter, than this required for realization of the laws of control transmission. The considered ways of the undertaking the full diagnostics automatic transmission by means of electronic control unit.
Keywords: гидроэлектромеханическая система; переключение передач; автоматическая трансмиссия; электронный блок управления; диагностика ГМТ; потенциометрические датчики